(untitled) (Ágora de Heterodoxias, 2025)
This article reports on a research study that aimed to identify the psychological risks associated with postoperative weight regain in patients who underwent bariatric surgery within the framework of the 2030 Agenda for Sustainable Development, which seeks to ensure healthy lives and promoting well-being. This agenda includes efforts to reduce mortality from noncommunicable diseases, such as obesity and overweight, with a particular emphasis on mental health. An interpretative approach was adopted, using a qualitative method and phenomenological design. The informants were three patients who had undergone bariatric surgery, reached a nadir ≥25%, and regained 15% of the total weight lost postoperatively. Data were collected through semi-structured interviews and analyzed using the hermeneutic method, categorization, theoretical triangulation and expert triangulation. The study concluded that there are common psychological risks among patients who experience weight loss: developmental traits and their impact on the self, emotional distress resulting from life experiences, patterns of attachment and personal attitudes, conceptions about obesity and bariatric surgery, and strategies and behaviors that influence weight and health